2009
DOI: 10.1590/s0036-36342009000300015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of the nested polymerase chain reaction in the diagnosis of extrapulmonary tuberculosis

Abstract: Objective. To evaluate the effectiveness of nested polymerase chain reaction (PCR) for diagnosis of extrapulmonary tuberculosis (ETB), as well as the impact of PCR results on clinical management. Materials and Methods. We conducted a study of nested PCR tests in 45 patients and a review of patient hospital files, calculating sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). Results. PCR was positive in 51% of cases; PCR sensitivity for diagnosing TB was 86%, specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…To confirm genitourinary TB (both in men and women) in urine samples, PCR targeting MPT-64 protein gene has earlier been demonstrated to be the most sensitive indicator as compared to intravenous urography, bladder biopsy or urine culture (Hemal et al, 2000). High sensitivity up to 100% has been claimed by nested PCR based on MTP-40 protein gene of M. tuberculosis (Garcia-Elorriaga et al, 2009). High sensitivity up to 100% has been claimed by nested PCR based on MTP-40 protein gene of M. tuberculosis (Garcia-Elorriaga et al, 2009).…”
Section: Genitourinary Tuberculosismentioning
confidence: 99%
“…To confirm genitourinary TB (both in men and women) in urine samples, PCR targeting MPT-64 protein gene has earlier been demonstrated to be the most sensitive indicator as compared to intravenous urography, bladder biopsy or urine culture (Hemal et al, 2000). High sensitivity up to 100% has been claimed by nested PCR based on MTP-40 protein gene of M. tuberculosis (Garcia-Elorriaga et al, 2009). High sensitivity up to 100% has been claimed by nested PCR based on MTP-40 protein gene of M. tuberculosis (Garcia-Elorriaga et al, 2009).…”
Section: Genitourinary Tuberculosismentioning
confidence: 99%
“…Earlier studies reported [16][17][18][19] the increased positivity by PCR targeting the IS6110 element in specimens of EPTB and 63%, 51%, 77% and 62% as positivity among EPTB specimens. In comparison, we found 72.6% positivity by PCR targeting the IS6110 element in specimens of EPTB.…”
Section: Discussionmentioning
confidence: 99%
“…Less sensitivity may arise when specimens contain very few mycobacteria. García et al, [17] Kolk et al, [21] Haron et al, [22] Pietrzak et al, [23] Singh et al [24] and Shukla et al [25] showed the detection of M. tuberculosis by PCR results as summarized in Table 2. Reported studies showed data of the positivity of the M. tuberculosis complex by IS6110 PCR on 50 to 250 sample size of EPTB case.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapulmonary TB (ETB) is an even greater diagnostic challenge than primary TB (PTB), as it occurs less frequently and with little liberation of bacilli. Thus, the combination of small numbers of bacilli and inaccessible sites makes bacteriological confirmation of extrapulmonary TB more difficult [7]. Also in ETB, fewer bacilli cause much greater damage secondary to bacterial invasion of solid organs, which induces severe immunological reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Also in ETB, fewer bacilli cause much greater damage secondary to bacterial invasion of solid organs, which induces severe immunological reactions. Thus, the combination of small numbers of bacilli and inaccessible sites makes bacteriological confirmation of extrapulmonary TB more difficult [7].…”
Section: Introductionmentioning
confidence: 99%